Serum Activins and Follistatin during the Treatment of Chronic Hepatitis C Genotypes 1 and 4 and Their Correlations with Viral Load and Liver Enzymes: A Preliminary Report - Bassem Refaat; Adel Galal El-Shemi; Ahmed Mohamed Ashshi; Adnan AlZanbagi (Gastroenterology Research and Practice)
Aims. To measure the effect of pegylated interferon-α therapy on serum activin-A, activin-B, and follistatin and their correlation with viral load and liver fibrosis in chronic hepatitis C (CHC). Methods. This study was cross-sectional and sera were collected from 165 participants classified into 7 groups: 40 healthy negative control, 33 treatment naïve patients as positive control, 19 patients at week 4, 22 at week 12, and 19 at week 24 of treatment initiation and 21 responders and 11 nonresponders at the end of 48-week treatment protocol. Serum candidate proteins were measured using ELISA and liver fibrosis was assessed by AST platelet ratio index (APRI). Results. CHC significantly increased activins and decreased follistatin compared to negative control (P<0.05). Activin-A and follistatin levels returned to the levels of negative control group at weeks 4, 12, and 24 following treatment initiation and were significantly different from positive control (P<0.05). Both proteins were significantly different between responders and nonresponders. Activin-A correlated positively and significantly with the viral load and APRI. Conclusion. CHC modulates serum activin-A and follistatin and they appear to be influenced by pegylated interferon-α therapy. Further studies are needed to explore the role of activins in CHC.